(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2020)
Daniel Solomon’s latest book of essays puts designing housing at the center of the design of cities; but he does not mean the banal towers which are the typical image of housing. He is advocating for communities built by carefully integrating new and old living places following a consistent street pattern and scale. China presents a test case for building such communities, and one of the most interesting parts of the book is an account of Solomon’s attempt to introduce community into the Chinese housing system, by meeting all the official criteria that has created hundreds of thousands of repetitive housing towers, but turning these prescriptions in a better direction.